Comparing the economic, energy, and environmental impacts of biodiesel versus petroleum diesel fuel use in construction equipment - Lewis, Phil; Karimi, Boshra; Shan, Yongwei; Rasdorf, William (International journal of construction education and research, 2019)
Advocates for biodiesel claim that it is a clean, renewable, and cost effective fuel that provides economic and environmental benefits while easing the energy impacts of petroleum diesel; however, these claims are often anecdotal in nature and may not be based on empirical data. This paper presents the results of a case study that analyzes the economic, energy, and environmental impacts of biodiesel versus petroleum diesel fuel use in construction equipment. Using real world data, statistical comparisons were performed on a fleet of backhoes, motor graders, and wheel loaders. Hypothesis testing was used to determine whether or not there was a statistically significant difference between B20 and petroleum diesel in fuel prices, fuel use rates, and emissions rates. Scatterplots were developed to show how the two fuels are related to each other. Results indicated that there was no statistically significant difference between the national average prices of B20 and petroleum diesel; however, there were statistically significant differences between B20 and petroleum diesel for fuel use rates and emissions rates. It was concluded that B20 has slightly higher economic and energy impacts than petroleum diesel, but B20 did show potential for lower emissions rates for some pollutants.